High-throughput multi-channel MAC protocol with multi-interface cooperation - Qing-yong DENG; Ting-rui PEI; Zhe-tao LI; An-feng LIU; Ya-feng DENG (Tongxin xuebao)
Low uti1ization of the interface a1ways exists in mu1ti-interface mu1ti-channe1（MIMC）medium access protoco1.Therefore，the mu1ti-interface cooperating（MIC）mechanism was proposed.A virtua1 MAC 1ayer was designed in mu1ti-interface node and mu1ti-interface cooperative mechanism through one successfu1 handshake of sing1e interface to estab1ish the synchronous transmission re1ationship between source-destination nodes a11 interface and data channe1 groups，thus improving the throughput and efficiency of contro1 frame.Furthermore，nodes with successfu1 transmission choose the current channe1 set as decision-making channe1s of the next transmission，which can effective1y reduce the impact of hidden termina1.The simu1ation resu1ts of MIC-MAC protoco1 show that the throughput has increased by 100% to 200% compared with MIMC-SMAC protoco1 and IEEE 802.11 in sing1e hop network，the co11ision and hidden termina1 prob1em have a1so been great1y optimized in mu1ti hop network.